De politiske spil omkring OL i Beijing 2008 - hvorfor blev de så dagsordensættende, og hvilke virkninger fik de? - Østergaard, Clemens Stubbe (Forum for Idræt, 2009)
Artiklen tager udgangspunkt i to problemstillinger i forhold til OL I Kina 2008, Hvordan kunne de mange spredte aktører især ngo’er, få så stor indflydelse på dagsordenen, som tilfældet blev? og Hvilke formål lå bag de mange forskellige aktiviteter, og hvordan kan man forklare variationerne i opnåelsen af disse mål? The political debate on the Beijing-games What did participation in the Olympic Games in Beijing, and the preceding debates, mean for the desire to advance human rights in China? An analysis of the question needs to be set in the larger context of the many national and international political games played out. Two main problems are analysed: how could the many dispersed actors, particularly NGOs, set the agenda so decisively? What goals were pursued, and how can we account for the variations in goalattainment? The answer to the first problem relies on the concept of (negative) »framing«, with the ever more concentrated international mass-media amplifying the agenda-setting capacity of the NGOs. A new element is that »boundary spanners« enable the Chinese population to discern the bias inherent in negative framing, thus affecting internal responses. The second question is answered by arguing that there were several categories of goals ranging from idealistic/religious, over purely organizational to political or foreign policy goals. Goal attainment was affected by whether the goals of actors were related to change in China or outside, whether media-bias was observed, and whether questions affecting nationalism and sovereignty were touched on. The analysis also discusses the influence of concepts like »group politics« and »soft power«. The analysis is based on media, on surveys and on interviews. It finds that human rights goals of NGOs were not furthered, whereas there may be a positive long-term effect of the successful games themselves. On organizational goals, it may also be too early to conclude. Concrete political goals, regarding for instance Darfur, Tibet or Xinjiang, registered no progress, on the contrary, but the likely US aim of reducing China’s growing »soft power« did have some success, at least in Western countries. A number of conclusions are drawn from the paradox of strong agendas- setting but little effect in China.